The Hesed and Rahamim of God as resources of hope in contexts of individual and communal loss : a multi-dimensional reading of Lamentations - Muriwo, Golden (Stellenbosch : Stellenbosch University, 2017)
Thesis (PhD)--Stellenbosch University, 2017.